Interleukin-9 mediates chronic kidney disease-dependent vein graft disease: a role for mast cells. Issue 13 (31st August 2017) - Zhang, Lisheng; Wu, Jiao-Hui; Otto, James C.; Gurley, Susan B.; Hauser, Elizabeth R.; Shenoy, Sudha K.; Nagi, Karim; Brian, Leigh; Wertman, Virginia; Mattocks, Natalie; Lawson, Jeffrey H.; Freedman, Neil J.
Abstract: Aims: Chronic kidney disease (CKD) is a powerful independent risk factor for cardiovascular events, including vein graft failure. Because CKD impairs the clearance of small proteins, we tested the hypothesis that CKD exacerbates vein graft disease by elevating serum levels of critical cytokines that promote vein graft neointimal hyperplasia. Methods and results: We modelled CKD in C57BL/6 mice with 5/6ths nephrectomy, which reduced glomerular filtration rate by 60%, and we modelled vein grafting with inferior-vena-cava-to-carotid interposition grafting. CKD increased vein graft neointimal hyperplasia four-fold, decreased vein graft re-endothelialization two-fold, and increased serum levels of interleukin-9 (IL-9) five-fold. By quantitative immunofluorescence and histochemical staining, vein grafts from CKD mice demonstrated a ∼two-fold higher prevalence of mast cells, and a six-fold higher prevalence of activated mast cells. Concordantly, vein grafts from CKD mice showed higher levels of TNF and NFκB activation, as judged by phosphorylation of NFκB p65 on Ser536 and by expression of VCAM-1. Arteriovenous fistula veins from humans with CKD also showed up-regulation of mast cells and IL-9. Treating CKD mice with IL-9-neutralizing IgG reduced vein graft neointimal area four-fold, increased vein graft re-endothelialization ∼two-fold, and reduced vein graft total and activated mast cell levels two- and four-fold, respectively. Treating CKD mice with the mast cell stabilizer cromolyn reduced neointimal hyperplasia and increased re-endothelialization in vein grafts. In vitro, IL-9 promoted endothelial cell apoptosis but had no effect on smooth muscle cell proliferation. Conclusion: CKD aggravates vein graft disease through mechanisms involving IL-9 and mast cell activation.